Factors Affecting Ovipositional Behaviour of Scutellista cyanea, an Egg-parasitoid of Hemispherical Scale - Ibrahim, Abdul Ghani (1984)
Scutellista cyanea Motschulsky is an egg parasitoid of many coccids, including the hemispherical scale, Saissetia coffeae. The adult female parasitoid oviposits in gravid scale, S. coffeae. Ambient temperature influences the number of eggs deposited and adult longevity of the parasitoid. The life-spcm of the adult parasitoid was found to be reduced with an increase in temperature; at 200 C longevity it was 80.0 days while at 28°C it was only 30 days. On the other hand, an increase in temperature within limits would increase the total number of eggs deposited by the parasitoid. In a comparison of two sizes of host-scale i.e. scale >3.5mm in length and <2.5mm in length, the result showed that significantly (p<0.05) greater parasitoid progency emerged from host scale of >3.5mm in length. The relationship between head width and adult longevity and between head width and egg production are r=0.90 and r=0.93.